Future of CBDC in India: Challenges, Opportunities, Risk & Awareness - Anandan, Manjari (Digital Repository of Theses, 2024)
Central Bank Digital Currency (CBDC) is a digital form of currency that is issued by the central bank of a country. The concept of CBDC has gained significant attention in recent years due to the increasing adoption of digital payment systems and the need for a secure and efficient payment system. In this research paper thesis, we examine the potential of CBDC in the Indian banking sector, highlighting the challenges, opportunities, security, and risk associated with its implementation. The thesis provides a comprehensive analysis of the Indian banking sector, including the current state of digital payments, the role of the central bank, and the regulatory environment. We discuss the potential benefits of CBDC in India, such as reduced transaction costs, improved financial inclusion, and greater transparency. However, we also address the challenges associated with CBDC implementation, including technological infrastructure, interoperability, privacy concerns, and the potential impact on monetary policy. We also analyze the security and risk implications of CBDC, such as cyber threats, fraud, and money laundering, perception and awareness of CBDC among Indian population The paper thesis concludes by providing recommendations for the implementation of CBDC in India, including the need for a phased approach, a robust regulatory framework, and investment in technological infrastructure. The potential impact of CBDC on the Indian economy and the banking sector is significant, and its successful implementation will require collaboration between the government, central bank, and financial institutions.